IMPLEMENTASI KURIKULUM MERDEKA DALAM MEMBANGUN GENERASI UNGGUL DAN ISLAMI MENUJU ERA SOCIETY 5.0 - Riskiyah, Eka Maftuhatil; Fariyanti, Alfiya; Abidin, Zeinal (An-Nadzir : Jurnal Manajemen Pendidikan Islam, 2024)
The curriculum as a plan in the education unit has an important role in the continuity process of education. Thus, it is necessary to discuss the independent curriculum implemented in 2022 as a preparation for the younger generation in facing the era of society 5.0. This research uses a qualitative method with a literature study research type. Data was obtained through articles, books, and previous research. The results and discussion of this research show that the independent curriculum is an improvement and refinement of the 2013 curriculum. This curriculum is centered on human resources so that human resources can improve their quality easily. The application of this independent curriculum is not only in one unit of education but all levels of education from elementary, secondary and tertiary levels. Returning to the purpose of the independent curriculum as a foundation for generations to be able to face the 5.0 era, it is known that the first superior and Islamic generation or human resources have literacy skills, secondly master technology and information, thirdly having good emotional intelligence and lastly having good spirituality.